Using picture-based chat in Edmodo social learning platform as a vocabulary learning strategy - Suyono, Achmad (JLT: Jurnal Linguistik Terapan, 2018)
The development of information and communication technologies has increased the opportunities for teachers to present learning experience which go beyond the classic face-to-face classroom interaction. By using appropriate teachnology, like a smartphone and an appropriate educational application, teachers can interact with their students and deliver text-based or multimedia learning activities. Edmodo is an example of such technology and has been gaining popularity among teachers and students. In English learning environment, Edmodo can be used to offer various learning activities and one of them is picture-based chat. In this chat, students are involved in conversation which is based on a selected picture posted by the students in turns. This strategy is expected to offer not only better retention of the vocabulary but also high level of interaction and participation among students. To provide more information about this strategy, this article is going to explore the advantages of picture-based chat in vocabulary learning and how to design the picture-based chat instruction so that it can promote effective vocabulary learning.